Dual-responsive nanoparticles based on chitosan for enhanced breast cancer therapy. (1st October 2019) - Zhang, Xuejing; Niu, Shiwei; Williams, Gareth R.; Wu, Jianrong; Chen, Xia; Zheng, Hong; Zhu, Li-Min
Highlights: Dual-responsive paclitaxel-loaded nanoparticles (NPs) based on chitosan were fabricated. These allowed hyaluronic acid-mediated targeting of CD44-overexpressing breast cancer cells. The NPs showed great promise in breast cancer therapy, both in vitro and in vivo. Abstract: In this study, we report a novel pH and temperature responsive paclitaxel-loaded drug delivery system based on chitosan and di(ethylene glycol) methyl ether methacrylate. This was functionalized with hyaluronic acid to permit active targeting of CD44-overexpressing human breast cancer cells. The resultant HA-CS-g-PDEGMA-PTX nanoparticles (NPs) have small and uniform sizes (˜170 nm), a high drug loading (13.6 ± 1.3%) and high encapsulation efficiency (76.2 ± 8.5%). Cell viability and confocal microscopy experiments demonstrated that the NPs could effectively target and kill MDA-MB-231 human breast cancer cells, but were much less toxic to healthy human umbilical vein endothelial cells. In vivo biodistribution studies in mice showed that the NPs accumulated in the tumor site, while free drug was distributed more widely and rapidly cleared from the body. Histopathological studies revealed that the NPs led to enhanced apoptosis in the tumor site, which resulted in reduced tumor growth. The NPs prepared in this work have great potential for the treatment of breast cancers, and further offer a platform with which to target other cancers.